표준화환자를 활용한 당뇨식이교육 동영상학습이 간호학생의 임상수행능력과 학습만족도에 미치는 효과 - 현경선; 강현숙; 김원옥; 박선희; 이지아; 석소현; Hyun, Kyung-Sun; Kang, Hyun-Sook; Kim, Won-Ock; Park, Sun-Hee; Lee, Ji-A; Sok, So-Hyune (Journal of Korean Academy of Nursing, 2009)
Purpose: The purpose of this study was to develop a multimedia learning program for patients with diabetes mellitus (DM) diet education using standardized patients and to examine the effects of the program on educational skills, communication skills, DM diet knowledge and learning satisfaction. Methods: The study employed a randomized control posttest non-synchronized design. The participants were 108 third year nursing students (52 experimental group, 56 control group) at K university in Seoul, Korea. The experimental group had regular lectures and the multimedia learning program for DM diet education using standardized patients while the control group had regular lectures only. The DM educational skills were measured by trained research assistants. Results: The students who received the multimedia learning program scored higher for DM diet educational skills, communication skills and DM diet knowledge compared to the control group. Learning satisfaction of the experimental group was higher than the control group, but statistically insignificant. Conclusion: Clinical competency was improved for students receiving the multimedia learning program for DM diet education using standardized patients, but there was no statistically significant effect on learning satisfaction. In the nursing education system there is a need to develop and apply more multimedia materials for education and to use standardized patients effectively.